HYPOGONADOTROPHIC HYPOGONADISM - A CASE REPORT - T, Qing Yu; L, Song Hai (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Hypogonadotrophic hypogonadism (HH) is a rare condition usually affecting the males. The estimated incidence is 1-10:100000 live births. Common presentations are infertility and delayed puberty. CASE We report a case of HH who has been followed up for the past 17 years since birth. The clinical courses including presenting features, diagnosis and management will be described. The patient was referred for micropenis with left retractile gonad at birth. Initial investigations showed a normal male karyotype of 46XY, low testosterone level and normal renal ultrasonography. Gonadotrophins were not available. There was history of micropenis in the maternal family member. He was subsequently followed up as outpatient for under-virilised male. At the age of 4, left orchidopexy was done. MRI pituitary was done to rule out central defect and noted to be normal. Human chorionic gonadotrophin stimulation test was done and showed poor testicular response. His growth parameter has always been within the normal centile. Other pituitary hormones were normal. At 12 years old, he was noted still prepubertal. Gonadotrophin releasing hormone test revealed a poor gonadotrophin response and diagnosis was made. Retrospectively, he did report poor sense of smell. He was started on intramuscular testosterone therapy at 12.5 years. Puberty progressed with induction and he achieved stage five of Tanner staging at 15 years old. However, his testes remained small and penile length is less than 2.5 standard deviation below the adult mean. CONCLUSION This is likely a congenital HH which involves lifelong treatment and monitoring. Early diagnosis allows better counselling and preparation for the family and patient throughout the course of disease.